Evaluation of small‐scale yielding boundary using digital image correlation results. Issue 4 (14th February 2022) - Vasco‐Olmo, Jose M.; Díaz, Francisco A.; Neto, Diogo M.; Sérgio, Edmundo R.; Antunes, Fernando V.; James, M. Neil
Abstract: In this work, the boundaries of small‐scale yielding (SSY) and large‐scale yielding (LSY) have been experimentally evaluated from the analysis of crack tip opening displacement (CTOD) measured by digital image correlation (DIC). According to a previous numerical work, the ratio between the elastic CTOD range and the total CTOD range (Δ δ e /Δ δ t ) defines the boundaries of SSY conditions and LSY. Three materials have been studied, commercially pure titanium and 2024‐T3 and 7050‐T6 aluminum alloys, tested at different stress ratio values. SSY conditions are shown to dominate when Δ δ e /Δ δ t  ≥ 79% and ≥78% for titanium and the two aluminum alloys, respectively. In addition, LSY can be established when Δ δ e /Δ δ t  ≤ 66.3% and ≤67.2% for titanium and for 2024‐T3 and 7050‐T6 aluminum alloys, respectively. Transition or LSY conditions are more probable in fatigue tests conducted at low R ratio and for crack lengths above 40% with respect to the width of the specimen. Highlights: The boundaries of small‐scale yielding (SSY) and large‐scale yielding (LSY) are defined using CTOD values obtained by digital image correlation (DIC). The materials studied were titanium and two aluminum alloys (AA): 2024‐T3 and 7050‐T6. SSY conditions are shown to dominate when Δδ e / Δδ t  ≥ 79% (Ti) and ≥78% (AA). LSY can be established when Δδ e / Δδ t  ≤ 66.3% (Ti) and ≤67.2% (AA). Transition or LSY conditions are more probable at low R ratio and large crack lengths.